Maternal exposure to childhood abuse is associated with elevated risk of autism - Roberts, Andrea L. (2013)
CONTEXT: Adverse perinatal circumstances have been associated with increased risk of autism. Women exposed to childhood abuse experience more adverse perinatal circumstances than women unexposed, but whether abuse is associated with autism in offspring is unknown. OBJECTIVE: To determine whether maternal exposure to childhood abuse is associated with risk of autism, and whether possible increased risk is accounted for by higher prevalence of adverse perinatal circumstances among abused women, including gestational diabetes, preeclampsia, selective serotonin reuptake inhibitor use, intimate partner abuse, prior abortion, pregnancy less than 37 weeks, low birth weight, alcohol use, and smoking during pregnancy. DESIGN AND SETTING: Nurses’ Health Study II, a population-based longitudinal cohort of 116,430 women. PATIENTS OR OTHER PARTICIPANTS: Participants with data on childhood abuse and child’s autism status (97% White). Controls were randomly selected from among children of women who did not report autism in offspring (N mothers of children with autism = 451; N mothers of children without autism=52,498). MAIN OUTCOME MEASURE: Autism spectrum disorder, assessed by maternal report, validated with the Autism Diagnostic Interview-Revised in a subsample. RESULTS: Exposure to abuse was associated with increased risk of autism in children in a monotonically increasing fashion. The highest level of abuse was associated with the greatest prevalence of autism (1.8% versus 0.7% in women not abused, P = 0.005) and the greatest risk for autism adjusted for demographic factors (risk ratio=3.7, 95% confidence interval=2.3, 5.8). All adverse perinatal circumstances were more prevalent in women abused except low birth weight. Adjusted for perinatal factors, the association of maternal abuse with autism was slightly attenuated (highest level of abuse, risk ratio = 3.0, 95% confidence interval=1.9, 4.9). CONCLUSIONS: We identify an intergenerational association between childhood exposure to abuse and risk for autism in the subsequent generation. Adverse perinatal circumstances accounted for only a small portion of this increased risk.